Chemopreventive effects of wild carrot oil against 7,12-dimethyl benz(a)anthracene-induced squamous cell carcinoma in mice - Abu Zeinab, Rami (2011)
Context: Daucus carota L. ssp. carota (Apiacea) is widely distributed throughout the world and has many uses in traditional medicine. Objective: The present study investigates the chemopreventive effects of oil extract of D. carota umbels on 7,12-dimethyl benz(a)anthracene (DMBA)-induced skin cancer in mice. Materials and methods: D. carota oil extract (DCOE) was prepared by extracting the dried umbels with 50:50 acetone:methanol. Skin papilloma were initiated by DMBA and promoted by 12-O-tetradecanoyl phorobol-13-acetate (TPA). The extract was administered to animals via gavage (0.02 mL of 100% oil), intraperitoneal (0.3 mL of 2% oil), and topical (0.2 mL of 5, 50, and 100% oil) routes for 20 weeks. Tumor appearance, incidence, yield, and volume were compared with those of a non-treated control group. Results: Topical 100% treatment delayed tumor appearance, and inhibited tumor incidence and yield by 40 and 89%, respectively. Topical 50% treatment inhibited tumor incidence and yield by 30 and 83%, respectively, whereas the 5% treatment inhibited tumor yield by 36%. Tumor volume was decreased by 99, 91, and 70% following topical treatments with 100, 50, and 5% oil, respectively. Intraperitoneal treatment inhibited tumor yield by 43%, and decreased tumor volume by 85%, whereas gavage treatment showed minimal effects on both. Intraperitoneal and topical treatment decreased infiltration and hyperplasia with an increase in the level of hyperkeratosis. Conclusion: These findings demonstrate that DCOE has remarkable antitumor activity against DMBA-induced skin cancer compared with non-treated animals paving the ground for further investigations.